Kintamani Bali Chinese Ethnic Religious Hybridity: A Dualism of Cultural Identity - hendra, Hendra Agus Prayoga; Khaidir, Afriva (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2023)
This research aim was to explore the form of religious hybridity carried out by the Kintamani Bali Chinese ethnic group as part of the diversity of Chinese ethnicity in Indonesia. Regarding religious hybridity in the Kintamani Balinese Chinese ethnic group, the reason for choosing this research was because the Balinese Chinese ethnicity is different from the Chinese Indonesian ethnicity in general; here they find unification and assimilation with Balinese culture, resulting in a dualism of cultural identity. This research used a qualitative approach with ethnographic methods, data collection through participant observation and in-depth interviews, and is supported by other secondary references. This research was analyzed using Homi Bhabha’s hybridity theory and Parson’s functional theory. Research results show since the arrival of ethnic Chinese in northern Bali, they have established economic and political relations with the Bangli kingdom, where there is a good relationship between ethnic Chinese and the king of Bangli, so that it has an impact on the social and cultural life of the Balinese Chinese ethnic, namely the existence of religious hybridity that occurs. The first can be seen in terms of religious rituals such as daily prayer activities, Second, there is hybridization in terms of places of worship, The third is hybridization in terms of religious ornaments and worship facilities. The causal factor is the first one amalgamation, a belief and philosophy of life for the Kintamani Chinese ethnic group, the existence of past history and open relationships, high tolerance, openness to differences, and not questioning religious issues. A new identity, namely the dualism of cultural identity attached to the Kintamani Chinese ethnic group. Therefore, this plays a role in the socio-cultural life of the village and creates harmony with the Balinese Hindu community.